ANALISIS VALUE FOR MONEY DALAM MENINGKATKAN MUTU PELAYANAN PUBLIK PADA STASIUN KERETA API SURABAYA KOTA - FILAILI HERAWATI, ARIEF Filaili (Jurnal Akuntansi AKUNESA, 2013)
Research aims to determine the influence of value for money in improving the qualityof public services at the railway station Surabaya Kota by using the methods ofdescriptive qualitative. The data type that used is the primary data and secondarydata. Primary data in the form of interviews and secondary data in the form ofannual report PT. Kereta Api Indonesia (Persero) 2011 period obtained from theofficial website of PT. Kereta Api Indonesia (Persero). The result showed that thereare inter - related relationship between value for money to improve the quality ofpublic services at the railway station Surabaya Kota.Keywords: Value for money, public services, railway station.